Mobile Banking Adoption in Rajshahi City: Key Factors Influencing Acceptance and Usage - Hossain, Dr. Md. Sumon; Taniya, Rabeya Khatun; Shams, Shahpar; Moulick, Dr. Raj Kumar; Uddin, Md. Shawan; Rana, Md. Sohel (Al-Qanṭara, 2025)
Purpose This quantitative study examines the factors influencing the acceptability of mobile banking in Rajshahi City, Bangladesh, using a positivist research approach. Design/methodology/approach Data were collected through convenience sampling with a structured questionnaire consisting of four phases. The analysis was conducted using SPSS version 23 and Partial Least Squares Structural Equation Modeling (PLS-SEM) to achieve the study's objectives. Findings The findings indicate that service quality, transaction speed, and ease of use positively influence customer satisfaction and loyalty. Conversely, dissatisfaction arises from the costs associated with credit card transactions and security concerns. By addressing these issues and optimizing costs, mobile banking experiences can be significantly improved. Originality/value Policymakers can utilize the findings to develop policies that encourage the adoption of mobile banking and address any barriers identified by the study. Limitation/Future Research Although the study has significant theoretical and practical implications, it is limited by a small sample size, focusing solely on a small town and using a cross-sectional design with primary data.